Diltiazem did not induce gingival overgrowth in rats: a clinical, histological and histometric analysis Diltiazem não induziu crescimento gengival em ratos: análise clínica, histológica e histométrica - Fernanda de Oliveira Bello Corrêa; Gabriela Giro; Daniela Gonçalves; Luis Carlos Spolidorio; Silvana Regina Perez Orrico (Sociedade Brasileira de Pesquisa Odontológica, 2005)
The administration of calcium channel blockers has been associated with gingival overgrowth. However, there are few studies in humans or animals that evaluated the effect of diltiazem on gingival tissues. The present study assessed the influence of diltiazem, at different dosages and treatment duration, on gingival tissues of rats, using clinical, histological and histometric analyses. Eighty young male rats were separated into eight groups according to the dosage and duration of treatment. Rats were treated for 20 or 40 days with a daily subcutaneous injection of 5, 20 or 50 mg/kg of body weight of diltiazem. The results confirmed that diltiazem did not induce gingival overgrowth in rats. For all animals, the evaluation did not show gingival alterations regardless of the dosages and periods of treatment. The histometric analysis showed no significant change in the area of epithelium and connective tissues, although after 40 days of treatment a decrease in the area of connective tissue was observed, without statistically significant difference from control groups. Within the limits of this study, we suggest that diltiazem did not induce gingival overgrowth. A administração de bloqueadores dos canais de cálcio tem sido associada com crescimento gengival; entretanto, existem poucos estudos em humanos e animais que avaliaram o efeito do diltiazem nos tecidos gengivais. O presente trabalho tem como objetivo avaliar o efeito do diltiazem, em diferentes dosagens e tempos de tratamento, no tecido gengival de ratos, por meio de análises clínica, histológica e histométrica. Oitenta ratos jovens machos foram divididos em oito grupos de acordo com a dosagem e o tempo de administração. Os animais foram tratados por 20 ou 40 dias com uma dosagem diária de diltiazem de 5, 20 ou 50 mg/kg de peso corporal, por via subcutânea. Os resultados confirmaram que o diltiazem não induziu crescimento gengival em ratos. Para todos os animais a avaliação não demonstrou alterações gengivais, independentemente da dosagem e do período de tratamento. A análise histométrica evidenciou ausência de alteração significante na área de tecidos epitelial e conjuntivo, embora, após 40 dias de tratamento, tenha sido observada diminuição na área de tecido conjuntivo, não significante estatisticamente. Dentro dos limites deste estudo, sugerimos que o diltiazem não induziu crescimento gengival.